The hasukjip: its history and current situation (2016)
The hasukjip (하숙집) is a form of small business in Korea. It consists of a house with several (sometimes up to a dozen or more) boarding rooms. Many Korean and foreign students living in hasukjips and Koreans understand hasukjips only as a type of private dormitory, but if we examine the example of changes in hasukjips we can also consider trends in Korean society. Although hasukjips reflect elements and aspects of various sides of life in Korea, Korean and foreign scholars have not undertaken research on the history of the hasukjip or changes in its history and this institution remains practically unknown in the Western academic world.The aim of this article is to consider elements of the history of the hasukjip and its place in Korean life.